The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1519-566x2005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Biologia de Spodoptera eridania (Cramer) (Lepidoptera: Noctuidae) em diferentes hospedeiros

Abstract: -Spodoptera eridania (Cramer) is a pest under expansion in cotton and soybean fields in the cerrado, and biology studies are needed on different hosts. In order to gain knowledge about the biology and leaf intake of S. eridania on cotton, soybean and morning glory (Ipomoea grandifolia), newly-hatched caterpillars were individualized and reared in the laboratory (27 ± 2 o C, R.H. 60 ± 10%, photophase of 14h). Parameters related to biology, leaf intake and reproduction were observed. The larval development perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
72
2
32

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 5 publications
13
72
2
32
Order By: Relevance
“…Foerster e Dionísio (1989) obtiveram período de incubação de seis dias, à temperatura de 20°C em bracatinga. Santos et al (2005), à temperatura de 27°C, obtiveram valores variando de 3,2 a 3,3 dias para algodoeiro, corda-de-viola e soja. A viabilidade dos ovos em morangueiro foi superior quando comparada à observada por Parra et al (1977) em soja e algodão, que foi de 58,57% e 47,89%, respectivamente, embora estas sejam semelhantes às obtidas para videira.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Foerster e Dionísio (1989) obtiveram período de incubação de seis dias, à temperatura de 20°C em bracatinga. Santos et al (2005), à temperatura de 27°C, obtiveram valores variando de 3,2 a 3,3 dias para algodoeiro, corda-de-viola e soja. A viabilidade dos ovos em morangueiro foi superior quando comparada à observada por Parra et al (1977) em soja e algodão, que foi de 58,57% e 47,89%, respectivamente, embora estas sejam semelhantes às obtidas para videira.…”
Section: Resultsunclassified
“…A viabilidade dos ovos em morangueiro foi superior quando comparada à observada por Parra et al (1977) em soja e algodão, que foi de 58,57% e 47,89%, respectivamente, embora estas sejam semelhantes às obtidas para videira. Considerando as duas espécies vegetais, as viabilidades foram inferiores às encontradas por Santos et al (2005) A duração média da fase de pupa foi de 12,2 (morangueiro) e 11,9 dias (videira) (P=0,3107) (Tabela 1), com diferença de um dia entre machos e fêmeas nas duas espécies (morangueiro: machos -12,6 e fêmeas -11,5 dias; videira: machos -12,4 e fêmeas -11,3 dias). O prolongamento do período pupal de machos também foi observado por Santos et al (2005) e Parra et al (1977), ambos em algodoeiro e soja.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…However, one must consider that there are great variations between values for the same species, especially due to temperature and host plant or artificial diet (i.e. Parra et al 1977, Mattana and Foerster 1988, Ali and Gaylor 1992, Greenberg et al 2001, Bavaresco et al 2003, Busato et al 2005, Santos et al 2005, Azidah and SofianAzirun 2006, Sá et al 2009, Barros et al 2010, Farahani et al 2011. Furthermore, Murúa et al (2008) showed huge variations between biological and reproductive parameters between cohorts of S. frugiperda from different locations and host plants in Argentina.…”
mentioning
confidence: 99%